MATHEMATICAL MODEL OF THE PLANNED EXPERIMENT FOR REGENERATION OF FILTER ELEMENTS BY THE METHOD OF GAS DESORPTION FROM WASHING LIQUID - Гаража, B. B.; Желіба, А. М. (Proceedings of National Aviation University (archive), 2021)
The mathematical model of the eight-factor planned experiment, verification of the adequacy of the model and verification of the significance of the regression coefficients are considered. Significant factors, matrix and plan of factorial experiment are given.